Validation of the health beliefs related to cardiovascular disease (HBCVD) scale and factors associated with health-promoting behaviour among single mothers in Kelantan - Yusof, Saidah Adilah Mohamed (2024)
Background: Cardiovascular disease (CVD) is the leading cause of death among women, with single mothers at higher risk due to psychosocial disadvantages. Belief in illness preventability significantly influences CVD risk and health-promoting behaviours (HPB). Objective: The current study aimed to translate and validate the health beliefs related to the cardiovascular disease (HBCVD) scale, determine the mean scores of HPB subscales, and assess the relationships between health beliefs, sociodemographic and comorbidities, and perceived social support with HPB among single mothers in Kelantan. Methodology: The study comprised two phases from May 2023 to April 2024. Phase one involved the translation and validation of the HBCVD scale. The forward and backward translation process was conducted by four translators. The validation process was performed by expert panels and a potential target population to obtain a Content Validity Index (CVI) and Face Validity Index (FVI). Construct validity using Confirmatory Factor Analysis (CFA) was conducted among 275 respondents using a robust maximum likelihood estimator. Meanwhile, the internal consistency reliability was examined based on composite reliability (Raykov’s rho). Subsequently, phase two was a cross-sectional study which involved 242 respondents who were randomly selected from four districts in Kelantan. The independent variables included sociodemographic factors, clinical profile, health beliefs related to CVD and perceived ocial supports. The dependent variable was the total HPB score. The data was then subjected to descriptive analysis and multiple linear regression for comprehensive evaluation of the predictors for HPB. Results: The CVI and FVI were 0.91 and 0.96, respectively. The factor loadings of each item were acceptable (> 0.4), and the fit indices from the final model of CFA resulted in a good model fit [SRMR = 0.054, RMSEA = 0.060 (90% CI: 0.050, 0.070, CFI = 0.931, TLI = 0.920]. The HBCVD-M showed good reliability, and the internal structure fit the model, with composite reliability ranging from 0.745 - 0.902. The total HPB score obtained by the respondents was 118.03 (19.2). The highest mean (SD) score was noted for spiritual growth, 22.46 (3.70), and for interpersonal relationships, 22.05 (3.67), and the lowest score was revealed in physical activity, 15.09 (4.62). Notably, perceived severity (adjusted β = 1.60; 95% CI: 0.68, 2.53; p < 0.001) and perceived social support (adjusted β = 0.63; 95% CI: 0.37, 0.90; p < 0.001) were positively related to HPB. In addition, educational level (adjusted β = -10.36; 95% CI: 16.06, 4.67; p < 0.001) and perceived benefits (adjusted β = -1.43; 95% CI: -2.37, -0.48; p < 0.001) were negatively related with HPB. Conclusion: The Malay version of HBCVD is a valid and reliable tool for measuring health beliefs among single mothers in Kelantan. Overall, the scores for HPB were moderate. Recognising the influential factors identified in the study could contribute to higher engagement in HPB and subsequently help reduce morbidity and mortality related to CVD.